Parallel Viterbi decoding methods for uncontrollable and controllable sources - Lin, H.-D.; Messerschmitt, D.G. (IEEE transactions on communications, 1993)
The parallel Viterbi decoding is discussed for two different cases: uncontrollable sources and controllable sources. For general, uncontrollable Markov processes, a previously known parallel method is extended to a hierarchical parallel decoding approach, which achieves a lower latency. For controllable Markov sources in telecommunications applications, new parallel decoding methods are obtained by controlling the source processes in appropriate ways. The focus is on the parallel decoding methods for controllable sources because these methods have zero processing overhead. Because the methods modify the coding process, they bring positive changes to framing and negative changes to latency and code performance. However, one can adjust the parameters of the methods to make the degradation negligible. Because of their low overhead, the methods are most attractive for high-speed decoders for convolutional and trellis codes, and they are also applicable to other sequential algorithms for suboptimal decoding and estimation of complex Markov sources.< >